2020
DOI: 10.21037/cdt-20-591
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of recombinant human brain natriuretic peptide on the myocardial injury induced by acute carbon monoxide poisoning

Abstract: Background: To investigate the protective effect of recombinant human brain natriuretic peptide (rhBNP) on myocardial injury after acute carbon monoxide poisoning (ACOP).Methods: We retrospectively reviewed medical records of patients with ACOP and high risk of cardiac events admitted to our hospital, and grouped them into rhBNP group and control group according treatments they received. Patients in control group received conventional treatment while those in rhBNP group were treated with rhBNP intravenously f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It mainly regulates hemodynamics by activating vascular endothelial protein kinase so as to promote vasodilation. Previous studies have proven that it is effective in treating myocardial infarction and other diseases [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…It mainly regulates hemodynamics by activating vascular endothelial protein kinase so as to promote vasodilation. Previous studies have proven that it is effective in treating myocardial infarction and other diseases [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the calcium-sensitizing effect of levosimendan is achieved by direct binding to troponin [Lin 2018]. Recombinant human BNP obviously reduces the levels of blood AST and CK-MB after reperfusion in patients with acute ST segment-elevation MI, indicating that it can protect cardiac function [Li 2020]. Both recombinant human BNP and levosimendan can lower AST levels in AMI patients undergoing emergency PCI, but the effect of the former was greater [Kreusser 2019].…”
Section: E6mentioning
confidence: 99%
“…[44,45] At the same time, injection of exogenous BNP also showed that recombinant human BNP improved cardiac function, increased ejection fraction, dilated vessels, and had antifibrotic effects. [46] In addition, a meta-analysis defining the predictors of sudden cardiac death and ventricular arrhythmia in patients with ICD found that high baseline BNP or N-terminal pro-BNP levels were independently associated with the occurrence of ventricular tachyarrhythmia. [47] Gene deletion experiments in mice have indicated that BNP preventing cardiac fibrosis.…”
Section: B-type Natriuretic Peptide Pathwaymentioning
confidence: 99%